A PRACTICAL PRE-OPERATIVE PREDICTIVE MODEL FOR DETERMINING HAMSTRING AUTOGRAFT SIZE FOR ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION IN CHILDREN AND ADOLESCENTS - Sherman, Benjamin (Orthop J Sports Med, 2020)
BACKGROUND: The most commonly used graft for pediatric/adolescent anterior cruciate ligament (ACL) reconstruction is the hamstring autograft. Recent evidence has suggested that graft sizes less than 8 mm and age less than 20 years old are the most significant factors influencing graft failure. Additionally, studies examining the role of augmenting smaller grafts with allograft have demonstrated mixed results and potentially increased failure rates. Efforts to predict hamstring size preoperatively using MRI and ultrasound in the adult population have shown promise. However, there have been no studies in an entirely pediatric population. HYPOTHESIS/PURPOSE: The purpose of this study was to evaluate the predictive value of MRI in determining hamstring autograft size preoperatively for pediatric ACL reconstructions. METHODS: Children and adolescents from 10-20 years old that had undergone ACL reconstruction using hamstring autograft were identified from 2017-2018. Semitendinosus and gracilis cross-sectional area and diameter were measured on preoperative knee MRIs using the field of interest and distance measurement tools. The slice used for measurement was identified as the largest section by the measuring surgeon. Two surgeons independently measured all MRIs. Preoperative demographic data (height, weight, body mass index (BMI), gender) and operative data (graft size) was collected. Ordinal regression analysis was performed to determine the relationship between demographic data and graft size. A Classification and Regression Tree (CART) was constructed to identify predictors for the pre-determined graft sizes of 8 mm. Receiver operating characteristics (ROC) analysis were then created to assess the performance of the predictive model and determine sensitivity and specificity. RESULTS: One hundred and ten children (54 boys, 56 girls) were included in this study with an average age of 15.93 years (range 11.81-20.22) and average BMI of 25.98 (range 16.02-40.08). CART analysis determined that if the sum of the cross-sectional areas of the semitendinosus and gracilis tendons were greater than 31.17 mm then 87.5% of children had graft sizes of 8 mm or greater. The ROC analysis determined the model to have an 80% sensitivity and 74% specificity for predicting a graft size of 8 mm or larger. CONCLUSION: A preoperative summation of the cross-sectional areas of the semitendinosus and gracilis tendons greater than 31.17 mm predicts an intraoperative graft size of 8 mm or larger in 87.5% of children.